2021
DOI: 10.14202/vetworld.2021.1559-1563
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and carcass characteristics of lambs fed fibrous agricultural wastes to substitute grass

Abstract: Background and Aim: Grass is often scarce for ruminants during the dry season in Indonesia; thus agricultural by-products are widely used as a substitute for grass. This study aimed to determine the effect of replacing Napier grass (NG) with agricultural by-products on the productivity and carcass characteristics of lambs. Materials and Methods: Twenty-four 3-month-old male lambs with initial body weights of 13.26±1.29 kg (coefficient of variation=9.73%) were allocated into a completely randomized design with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The results of the current study was same with Prima et al (2019) which showed that Thintailed lambs with 25.76 kg of slaughter weight had 6,700 g of meat weight. The meat weight in this study was higher than that of Purbowati et al (2021) which showed that Thin-Tailed lambs with 20.03 of slaughter weight had meat weight of 4,500 g. The results showed that the higher the level of feed, the lower the bone weight (P<0.01). Lambs fed T3 had the lowest bone weight (P<0.01) in comparison to that of T2 and that of T1.…”
Section: Productivitymentioning
confidence: 48%
See 2 more Smart Citations
“…The results of the current study was same with Prima et al (2019) which showed that Thintailed lambs with 25.76 kg of slaughter weight had 6,700 g of meat weight. The meat weight in this study was higher than that of Purbowati et al (2021) which showed that Thin-Tailed lambs with 20.03 of slaughter weight had meat weight of 4,500 g. The results showed that the higher the level of feed, the lower the bone weight (P<0.01). Lambs fed T3 had the lowest bone weight (P<0.01) in comparison to that of T2 and that of T1.…”
Section: Productivitymentioning
confidence: 48%
“…It was due to the lambs of T3 had a lot of nutrients to digest and could be metabolized and then deposited as subcutaneous fat and intermuscular fat. Study of Phrache et al (2022) and Purbowati et al (2021) showed that fat was deposited in most tissues in the body and in four parts, namely abdominal, subcutaneous, intermuscular and intramuscular. Paredes et al (2013) and Santos et al (2018) stated that the growth rate of fat tissue is still low at birth then slowly increases at first and increases more rapidly when the lambs reach maturity.…”
Section: Productivitymentioning
confidence: 98%
See 1 more Smart Citation
“…Dressing percentage is highly variable in small ruminants, ranging from 36% to about 60%, and depends on numerous factors, such as age, weight at slaughter, housing system, breed, and sex. Purbowati et al [ 21 ] reported that the average dressing percentage of thin-tailed sheep in Indonesia was 40%. Lamb quality parameters were significantly associated (p≤ 0.05) with pH value.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this diversity of corn cultivars, it has been successfully used as ready-to-use supplementary food (RUSF) aimed at improving the nutrition of moderate acute malnutrition (MAM) in children under five years old in Indonesia (Fetriyuna et al 2021). Also, the agricultural waste from corn has been used in the country to increase productivity and carcass characteristics of lambs (Purbowati et al 2021) and cattle (Tahuk et al 2020) fed with this fibrous agricultural waste as a substitute for regular grass. Furthermore, the use of corn to produce biodiesel for the United States market has caused changes in land use for cultivating corn in Malaysia and Indonesia, compared to other vegetables like soy (Taheripour and Tyner 2020).…”
Section: Introductionmentioning
confidence: 99%